A fluorescence resonance energy transfer (FRET)‐based redox sensor reveals physiological role of thioredoxin in the yeast Saccharomyces cerevisiae. Issue 6 (14th February 2013) - Oku, Masahide; Hoseki, Jun; Ichiki, Yayoi; Sakai, Yasuyoshi
Abstract : The physiological roles of the thioredoxin isozymes in the yeast Saccharomyces cerevisiae were investigated using a novel FRET‐based redox probe, Redoxfluor. After establishing responsiveness of the probe toward thioredoxin, we followed the fluorescence signal of Redoxfluor expressed in the yeast and found that one of the thioredoxin isozymes, Trx2, was required for maintaining the redox status when stationary culture of the organism was exposed to starvation and mild‐heat stresses. The failure to maintain redox balance under the tested condition preceded decreased viability of the trx2 mutants, indicating the functional importance of the cytoplasmic thioredoxin in adaptation to environmental changes. Abstract : ► Redoxfluor indicated reduced state in vitro by thioredoxin application. ► Starvation and mild‐heat stresses caused oxidized cytoplasmic state of trx2 mutants. ► The oxidized state in the stress condition preceded viability loss of trx2 mutants.